Changes in expression profiles of genes related to sexual maturation during spermatogenesis in testes of early-maturing male Atlantic salmon parr, Salmo salar - Maugars, Gersende; Schmitz, Monika (Société Française d'Ichtyologie, 2008)
We investigated the expression of genes encoding proteins involved in sex steroid biosynthesis (Ff1b, StAR, P450scc, 3b-HSD, P450c17, P45011b and11b-HS D and AMH homolog during early sexual maturation in male Atlantic salmon parr. Male salmon parrs were sampled during their first sexual maturation. Testicular gene expression was analyzed by quantitative RT-PCR. The expression of genes encoding Ff1b, StAR, P450scc, 3b-HSD, P450c17 and 11b-HSD was upregulated when spermatogenesis started. A general and testicular increase of the genes encoding steroidogenic proteins was measured during spermiogenesis. StAR mRNA levels increased strongly during spermatogenesis. In contrast, transcript levels of AMH started to decrease when spermatogonial proliferation was initiated. Coordinated de novo transcriptions of genes encoding StAR as well as the key steroidogenic enzymes and a suppression of AMH may be required for initiation and course of the spermatogenesis.